2015
DOI: 10.1002/ppul.23308
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum depression, a direct and mediating risk factor for preschool wheeze in girls

Abstract: Postpartum depression may be a risk factor for preschool wheeze among girls in a low risk population, directly and indirectly through prenatal distress and vitamin use. Interventions which target postpartum depression and promote a healthy pregnancy may also reduce the risk of wheeze in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 57 publications
(83 reference statements)
2
20
0
Order By: Relevance
“…When postnatal exposures were considered, maternal psychological distress, as well IPV exposure, were strongly associated with the child experiencing at least one episode of wheezing during the 24‐month period, as well as recurrent wheeze episodes. These results strengthen the findings of several studies reporting on the relationship between maternal psychosocial risk factors and childhood wheeze and asthma, and extend the association into a LMIC context.…”
Section: Discussionsupporting
confidence: 89%
“…When postnatal exposures were considered, maternal psychological distress, as well IPV exposure, were strongly associated with the child experiencing at least one episode of wheezing during the 24‐month period, as well as recurrent wheeze episodes. These results strengthen the findings of several studies reporting on the relationship between maternal psychosocial risk factors and childhood wheeze and asthma, and extend the association into a LMIC context.…”
Section: Discussionsupporting
confidence: 89%
“…New evidence from large, general population cohorts has extended these initial associations in several ways. Second, postpartum depression was found to mediate the association between prenatal distress and preschool wheeze in girls, but it also had a direct association with wheeze [17]. Second, postpartum depression was found to mediate the association between prenatal distress and preschool wheeze in girls, but it also had a direct association with wheeze [17].…”
Section: Introductionmentioning
confidence: 87%
“…First, maternal distress or anxiety during pregnancy was observed to be associated with preschool wheeze [15] but also with school-age asthma [16]. Second, postpartum depression was found to mediate the association between prenatal distress and preschool wheeze in girls, but it also had a direct association with wheeze [17]. Lastly, only maternal distress that persisted beyond the postnatal period has shown to increase the risk of asthma at 7 years of age [18], and Giallo et al [19] found this association to be independent of prenatal distress.…”
Section: Introductionmentioning
confidence: 99%
“…Modern living conditions include changing hygiene and exposure to air pollution, but also depression and stress. Alton et al investigated 791 women and their children at 3 years of age, to identify whether postpartum depression is a risk factor for preschool wheeze. Postpartum depression was present in about 8% of the women and it increased the risk of wheezing in girls but not boys.…”
Section: Asthmamentioning
confidence: 99%